Ferramentas didáticas para o(a) professor(a) designado(a) de Minas Gerais. Ensino de História, Mundos do Trabalho e Patrimônio Cultural em Uberlândia - Gimenes, Marcus Dias (2024)
This work aims to reflect on the precarious conditions of temporary contracts for History teachers in public state schools in Uberlândia/Minas Gerais and to develop didactic tools to help them work with important themes in High School education more effectively. To achieve this, it criticizes the neoliberal mercantilist-privatist public policies that have emerged since the 1990s, which seek to undermine public education and favor Civil Society Organizations. Given that these professionals do not have sufficient time for lesson planning, it is necessary to have supporting material that is easily accessible and well-organized to assist them in planning their classes and, consequently, to prioritize the quality of education. The intended didactic material focuses on heritage education, aiming to establish a connection between History, memory, heritage, and important topics taught in High School. Methodologically, in the initial stage, a bibliographic survey is conducted on the working conditions of temporary teachers, in dialogue with the current legislation in the State of Minas Gerais. Subsequently, the proposal for didactic material is developed so that teachers can work with the concept of historical and cultural heritage of the city of Uberlândia, starting from the history of one of the city's first neighborhoods, the Patrimônio Neighborhood. The work concludes that the undermining of the work of public education in the state of Minas Gerais holds a resemblance to the living conditions of the previously enslaved in the post-abolition period, despite the chronological distance and historical contexts that separate them.